Predictors of health care use by adults 50 years and over in a rural South African setting - Ameh, S; Kahn, K; Tollman, S.M; et al (My University, 2014)
BACKGROUND: South Africa's epidemiological transition is characterised by an increasing burden of chronic communicable and non-communicable diseases. However, little is known about predictors of health care use (HCU) for the prevention and control of chronic diseases among older adults. OBJECTIVE: To describe reported health problems and determine predictors of HCU by adults aged 50+ living in a rural sub-district of South Africa. DESIGN: A cross-sectional study to measure HCU was conducted in 2010 in the Agincourt sub-district of Mpumalanga Province, an area underpinned by a robust health and demographic surveillance system. HCU, socio-demographic variables, reception of social grants, and type of medical aid were measured, and compared between responders who used health care services with those who did not. Predictors of HCU were determined by binary logistic regression adjusted for socio-demographic variables. RESULTS: Seventy-five percent of the eligible adults aged 50+ responded to the survey. Average age of the targeted 7,870 older adults was 66 years (95% CI: 65.3, 65.8), and there were more women than men (70% vs. 30%, p<0.001). All 5,795 responders reported health problems, of which 96% used health care, predominantly at public health facilities (82%). Reported health problems were: chronic non-communicable diseases (41% - e.g. hypertension), acute conditions (27% - e.g. flu and fever), other conditions (26% - e.g. musculoskeletal pain), chronic communicable diseases (3% - e.g. HIV and TB), and injuries (3%). In multivariate logistic regression, responders with chronic communicable disease (OR=5.91, 95% CI: 1.44, 24.32) and non-communicable disease (OR=2.85, 95% CI: 1.96, 4.14) had significantly higher odds of using health care compared with those with acute conditions. Responders with six or more years of education had a two-fold increased odds of using health care (OR=2.49, 95% CI: 1.27, 4.86) compared with those with no formal education. CONCLUSION: Chronic communicable and non-communicable diseases were the most prevalent and main predictors of HCU in this population, suggesting prioritisation of public health care services for chronic diseases among older people in this rural setting.
KIM
Keywords: Rural Population; South Africa; Epidemiology; Delivery of Health Care